International consensus on methotrexate dosing for patients with atopic dermatitis: An eDelphi study. - Caron, Anouk G.M.; van Huizen, Astrid M.; Musters, Annelie A.H.; Gerbens, Louise A.A.; Middelkamp Hup, Maritza A.; Flohr, Carsten; Irvine, Alan D.; Vestergaard, Christian; Peris, Ketty; Brandling-Bennett, Heather A.; Drucker, Aaron M.; Spuls, Phyllis I.; et al. (Journal of the European Academy of Dermatology and Venereology, 2025)
BACKGROUND: Despite the widespread off-label use of methotrexate (MTX) for the treatment of atopic dermatitis (AD), there is limited high-quality evidence on dosing regimens and existing guidelines do not provide clear recommendations regarding dosing strategies. OBJECTIVE: The aim of this study was to achieve international consensus among AD experts to standardize the dosing regimen for MTX treatment in adults and children with AD. METHODS: An electronic Delphi (eDelphi) study was conducted from October 2021 to September 2022. Recruitment was conducted through dermatology societies and AD interest groups. Participation was open to dermatologists and dermatology residents experienced in treating AD patients with MTX. The study consisted of three online rounds. The first round was informed by a systematic review of relevant literature, and subsequent rounds were adjusted based on the results of the previous round. Participants voted on 19 proposals using a 9-point scale (1-3 disagree, 4-6 neither agree nor disagree, 7-9 agree). Consensus was achieved when at least 70% of participants agreed, and less than 15% disagreed. Proposals that did not reach consensus in the first three rounds were discussed in a consensus meeting, where consensus was defined as less than 30% disagreement. RESULTS: In total, 152 participants completed Round 1, 104 (68%) completed all survey rounds, and 43 (28%) joined the consensus meeting. Consensus was achieved on 7 proposals in Round 1, 4 in Round 2 and 6 in Round 3. The final 2 proposals reached consensus during the consensus meeting. Consensus topics include test dose, start dose, maximum dose, administration route, dosing schedule, management of stopping treatment, treatment duration and folic acid supplementation. CONCLUSIONS: This eDelphi study achieved consensus on 19 proposals related to MTX dosing for adults and children with AD. These results aim to guide prescribing decisions and encourage a standardized global approach to MTX use in AD.
EVALuna2:587464